Potensi Pemanfaatan Limbah Tulang Ikan Sunu (Plectropomus Leopardus): Analisis FTIR dan XRF untuk Karakterisasi Serbuk Material - Rani, Sefrilita Risqi Adikaning; Ihsan, Ihsan; Asriani, Asriani; Putri, Ananda Anidya (JFT: Jurnal Fisika dan Terapannya, 2025)
This study aims to investigate the potential utilization of fish bone waste from Sunu as a material source through characterization analysis using FTIR (Fourier Transform Infrared Spectroscopy) and XRF (X-ray Fluorescence). The results of the FTIR analysis show characteristic peaks indicating the presence of important functional groups such as hydroxyl, phosphate, and carbonate. The presence of calcium phosphate as a major component suggests the potential of this bone powder for biomedical applications, such as the production of bone implants and bioceramic materials. Additionally, the XRF analysis reveals high concentrations of calcium (84.8%) and phosphorus (13.5%), along with other relevant oxides, indicating its potential use as a nutritional supplement and building material. Overall, this study demonstrates that fish bone powder from Sunu holds significant potential for applications in the fields of health, food, and composite materials, while also supporting sustainability in fisheries waste management.